Peningkatan Potensi Pelaku Wisata Dalam Mengelola Desa Wisata Menuju Kebangkitan dan Kemajuan di Tengah Pandemi - Filda Rahmiati; Purwanto (Rural Development For Economic Resilience (RUDENCE), 2021)
ABSTRACT This community service activity is our contribution to the community, especially for tourism actors in tourist villages affected during the COVID-19 pandemic. This community service activity is in the form of a webinar that aims to provide an understanding of strategies in managing Tourism Villages for the revival and progress of the village itself in order to provide an understanding to the outside community about how to manage village assets in addition to increasing community knowledge and understanding on how to optimize village management. using the principle of 'Leadership' that exists in tourist villages. The number of participants in this webinar exceeded the target, which was more than 200 participants with diverse backgrounds, from students, tourism village businessmen, to government agencies such as the ministry and Bappeda. Positive responses were obtained from the participants that this webinar activity provided knowledge as well as enlightenment and enthusiasm to re-build a tourist village with the hope that in the future it can further increase the number of tourists visiting which will certainly have an impact on improving the economy of rural communities.   ABSTRAK Kegiatan pengabdian masyarakat ini merupakan sumbangsih kami kepada masyarakat khususnya bagi pelaku wisata pada desa wisata yang terdampak selama masa pandemi covid-19. Kegiatan pengabdian masyarakat ini berupa webinar yang bertujuan untuk memberikan pemahaman mengenai strategi dalam mengelola Desa Wisata demi kebangkitan dan kemajuan desa itu sendiri guna memberi pemahaman kepada masyarakat luar mengenai cara mengelola aset desa selain itu, untuk meningkatkan pengetahuan dan pemahaman masyarakat tentang cara bagaimana mengptimalkan pengelolaan desa menggunakan prinsip ‘Leadership’ yang ada di desa wisata. Jumlah partisipan pada webinar ini melebihi target yaitu lebih dari 200 partisipan dengan latar belakang yang beragam dari mahasiswa, pelaku usaha desa wisata, hingga pihak pemerintah seperti kementrian juga bappeda. Tanggapan positif didapat dari para partisipan bahwa kegiatan webinar ini memberikan pengetahuan juga pencerahan dan semangat untuk kembali membangun desa wisata dengan harapan di masa mendatang dapat lebih meningkatkan jumlah wisatawan yang berkunjung yang pastinya berdampak pada peningkatan perekonomian masyarakat desa.